Preoperative Systemic Corticosteroids and Intraoperative Outcomes for Endoscopic Sinus Surgery:A Meta-Analysis of Randomized Controlled Trials - Bimo Wiratomo Baskoro; Ja'far Elyas; Dinda Puspha; Nabil Ramaseno; Mahdi Syahputra Imam; Khairan Irmansyah; Ilham Syahputro (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) often requires endoscopic sinus surgery (ESS) when medical therapy fails. Preoperative systemic corticosteroids are commonly administered to reduce mucosal inflammation and polyp size; however, their effects on intraoperative outcomes remain uncertain. Objective: To evaluate the effects of preoperative systemic corticosteroids on surgical field quality, intraoperative blood loss, and operative time during ESS for CRSwNP. Methods: A systematic review and meta-analysis of randomized controlled trials was conducted in accordance with PRISMA 2020 guidelines and registered in PROSPERO (CRD420241330602). Electronic databases were searched from inception to the final search date. Eligible studies included adults with CRSwNP undergoing ESS who received preoperative systemic corticosteroids. The primary outcome was surgical field quality, while secondary outcomes included intraoperative blood loss and operative time. Two reviewers independently performed study selection, data extraction, and risk-of-bias assessment. Random-effects meta-analysis was used to pool standardized mean differences (SMDs) and mean differences (MDs). Results: Five randomized controlled trials involving 242 participants were included. Preoperative corticosteroids significantly reduced intraoperative blood loss (MD −80.42 mL; 95% CI, −158.47 to −2.37; p = 0.04) and operative time (MD −10.84 minutes; 95% CI, −19.57 to −2.10; p = 0.02). Surgical field quality showed a favorable but non-significant improvement (SMD −1.12; 95% CI, −2.35 to 0.11; p = 0.08). Considerable heterogeneity was observed for blood loss and surgical field quality. Conclusion: Preoperative systemic corticosteroids may improve intraoperative outcomes during ESS by reducing blood loss and operative time, although their effect on surgical field quality remains uncertain. Further high-quality randomized trials are needed to determine the optimal corticosteroid regimen.